School knowledge and country people knowledge agreements and disagreements in the rural school - Claudia Marcela Peña (Corporación Universitaria Minuto de Dios, 2014)
This article proposes a theoretical reflection about the relationship between knowledge and expertise, from an epistemological perspective that explains the origin of each one, proposing a meeting point between the two in the rural school. Parting from certain questions, we analyze the fundamental points which guide us towards the discussion on whether the school is a carrier of a universe unrelated to the peasant, a kind of "urbanization" of the rural through it, taking into account that this is an urban phenomenon. From an anti-colonialist point of view, we ask about the possibility of refuting the epistemological assumptions that identifies the production of knowledge only within the Academy and within the canyons and paradigms established by the Western Science. In this sense, it is proposed that educational practice be thought and spearheaded from the rural context. It is here that the forms of knowledge production are taken into account and engaged in dialogue in the realm of extra-academic and extra-scientific areas that uphold the peasant's knowledge. We talk about a universe that contains ideas about the world, a worldview, ways of understanding nature and its relationship with man, knowledge, education and learning in the rural context that has been forgotten by Colombian society for decades.